so this is
Multiplying each term by (x- 4)(x- 2) gets rid of all the fractions.
Again, I am going to assume that you really mean . Once again, [tex]t^3+ 3t+ 2= (t+1)(t+ 2) so multiplying each term by (t+1)(t+2) gets rid of the fractions.32/t^2+3t+2 - 3 = t-3/t+1
Just go ahead and multiply it out: which is the same as 3r^2+ 11r+ 4= 0. Complete the square or use the quadratic formula.r(3-r) + (2r+2)^2 = 0
Why didn't you do that to begin with?!Can somebody help me with these please our midterm is tomorrow and if questions like these turn up (which is very likely) then my goose is cooked.
EDIT: I grouped them together to make things clearer:
(x+17)/(x^2-6x+8) + (x-2)/(x-4) = (x-4)/(x-2)
32/(t^2+3t+2) - 3 = (t-3)/(t+1)
r(3-r) + (2r+2)^2 = 0